UPAYA MANAJEMEN DALAM MENCEGAH DAN MENGATASI TERJADINYA PERSELISIHAN HUBUNGAN INDUSTRIAL - Nyayu Siti Rachmaliya (Sekolah Tinggi Manajemen IMMI, 2018)
The termination of employment for labor means the loss of a livelihood which means the beginning of the unemployment period with all its consequences, so as to ensure the certainty and security of the workforce there should be no termination of employment. However, in fact proves that termination of employment can not be prevented entirely the following article will explain about layoffs and its settlement according to the laws and regulations applicable in Indonesia method This writing uses descriptive method bydescribing the problem ofworking relationship and the settlement of the problem in layoffs Power Work has a very important role and position as the agent and the purpose of development. Law no. 13 of 2003 on Manpower is made to ensure the maintenance of laborers / workers' rights in an employment relationship, so there is no cruelty from the stronger to the weaker. Although barakaai protection of labor has not been maximally can be done by the government but we appreciate the existence of legal rules that can protect the interests of the workers. We hope that in the future the legislation will be made more perfect so that the welfare and protection of the workers can be more fulfilled